Feasibility and Efficacy of Carotid Stenting in Patients with Contralateral ICA Occlusion - Mehmet Cingöz; Mustafa Bal; Ali Dablan; Mustafa Fatih Arslan; Çağrı Erdim; Oğuzhan Türksayar; Tevfik Güzelbey (Bagcilar Medical Bulletin)
Objective: This study was conducted to assess the feasibility, safety, and efficacy of carotid artery stenting (CAS) in patients with severe ipsilateral carotid artery stenosis and contralateral internal carotid artery occlusion (CCO) and compare the outcomes with a matched control group without contralateral occlusion. Method: A retrospective study was conducted on 247 patients treated with CAS between April 2020 and July 2024. Of these, 21 patients with CCO were matched 1:1 to a control group without CCO based on age and sex. Procedural success, periprocedural complications, and short- to mid-term follow-up outcomes (median follow-up: 24 months) were analyzed. Results: Technical success was accomplished in every case. Two periprocedural complications were identified in each group. Three patients in the CCO group and two in the control group died during the follow-up, with myocardial infarction determined to be the cause of death in one patient from each group. No new ischemic cerebrovascular events were recorded in either group during the follow-up period. Conclusion: CAS is a feasible and effective treatment for patients with severe carotid stenosis and CCO, yielding outcomes comparable to patients without contralateral occlusion.